Efeito da morfologia das fibras das madeiras de Eucalyptus e Corymbia na produção e qualidade do carvão vegetal - Takarada, Luiz Mendes (2015)
This study aimed to evaluate the influence of the wood fiber morphology on the yield and charcoal quality. Woods from three genetic materials were used, the C. citriodora and two clones of natural hybrids of E. urophylla (VM04 and MN463). Each genetic material is represented by five trees with a mean diameter of the population. Sampling the stem considered both the radial (heartwood and sapwood) as the longitudinal variation. The materials were characterized anatomically and subsequently carbonized at a heating rate of 60°C hour-1 until the temperature of 400°C during 30 minutes. The charcoal produced was physically and chemically characterized, moreover was obtained gravimetric yield of carbonization. The results obtained, it was concluded that the MN 463 clone had the lowest gross calorific value, differing from the other genetic materials. The VM 04 clone got worse in the gravimetric charcoal yield. The C. citriodora obtained the highest values of apparent relative density (ARD) and energy density (ED). The sapwood presented gross calorific value (GCV) and ARD greater than the heartwood, but gravimetric charcoal yield (GCY) was higher in the heartwood. The immediate chemical composition of charcoal was not influenced by any of the factors evaluated. The GCY, ARD, length, width and thickness of the fiber wall, slenderness ratio, fraction wall and Runkel index showed a linear trend of decrease in longitudinal direction. The ARD showed a negative and significant correlation with the width, lumen diameter of the fiber and coefficient of flexibility and positive and significant correlation with slenderness ratio and wall fraction of the fiber. The ED was positively and significantly correlated with the width, lumen diameter of the fiber and coefficient of flexibility, having only a negative relationship with the wall fraction.